2008
DOI: 10.4049/jimmunol.180.5.3319
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial versus Immune Cell Stat1 Function for Innate Defense against Respiratory Viral Infection

Abstract: The epithelial surface is often proposed to actively participate in host defense, but the evidence remains circumstantial. Here we use a mouse paramyxovirus (Sendai virus; SeV) to show that a prominent early event in respiratory infection is activation of Stat1 in airway epithelial cells. Stat1−/– mice developed illness that resembled severe paramyxoviral respiratory infection in humans and was characterized by increased viral replication and neutrophilic inflammation in concert with overproduction of TNF‐α an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 50 publications
5
70
0
1
Order By: Relevance
“…It has been previously shown that neutrophils infi ltrate the lungs of SeV-infected mice. Neutrophils are the predominant cell present in the BALF until day 5, when macrophages and lymphocytes increase in number ( 24 ). The involvement of neutrophil activation and MPO-derived products in this model was verifi ed by showing that 2-ClHA accumulated in BALF collected from SeV-infected mice compared with control-treated mice.…”
Section: Production Of 2-clha In An Animal Model Of a Lower Respiratomentioning
confidence: 96%
See 3 more Smart Citations
“…It has been previously shown that neutrophils infi ltrate the lungs of SeV-infected mice. Neutrophils are the predominant cell present in the BALF until day 5, when macrophages and lymphocytes increase in number ( 24 ). The involvement of neutrophil activation and MPO-derived products in this model was verifi ed by showing that 2-ClHA accumulated in BALF collected from SeV-infected mice compared with control-treated mice.…”
Section: Production Of 2-clha In An Animal Model Of a Lower Respiratomentioning
confidence: 96%
“…Thus, experiments were performed to assess the accumulation of these lipids in a mouse model of respiratory viral infection that results in the recruitment and activation of neutrophils to the lung ( 24 ). SeVspecifi c RNA was present only in the lungs of SeV-infected mice, demonstrating virus replication.…”
Section: Production Of 2-clha In An Animal Model Of a Lower Respiratomentioning
confidence: 99%
See 2 more Smart Citations
“…The airway epithelium lining the respiratory tract not only represents the first barrier of defense against respiratory pathogens but is often the primary target of infection (1). Consequently, apart from a critical role in gas exchange function, airway epithelial cells additionally participate in host defense mechanisms by producing cytokines and chemokines (2)(3)(4)(5)(6)(7)(8). Since exacerbated responses by airway epithelial cells in response to innocuous antigens or pathogens can prove detrimental to lung function, airway epithelial cells have also evolved to regulate pulmonary homeostasis by multiple mechanisms, including, among others, expression of CD200 (9), MUC-1 (10), and surfactant proteins (11) and reduced expression of adaptor molecules (12)(13)(14).…”
mentioning
confidence: 99%